Knock on wood - Vornholt, John.; Scovell, Nell.; Schmock, Jonathan; Copyright Paperback Collection (Library of Congress) (New York : Pocket Books, 2000)
After the Westbridge High football team wins an amazing two games in a row, the whole team becomes superstitious. But the teammates take things a little two far by refusing to shower or change their socks and underwear, thinking it will bring them more good luck. Sabrina and Dreama ask Principal Kraft to curb the boys' bad hygiene, but he thinks that if the football team continues to win, they can be as smelly as they want to be! So Sabrina and the Dreama decide to teach the guys a lesson to show them how silly it is to be superstitious. But their plan backfires. Can Sabrina fix the problem or will the people of Westbridge have to be forever wary of breaking mirrors and walking under ladders?
"An Archway paperback."
"Based on the hit TV series"--Cover.
"Based on characters in Archie Comics and based upon the television series Sabrina, the Teenage Witch, created for television by Nell Scovel, developed for television by Jonathan Schmock."
Keywords: Occult fiction; Teenage girls -- Fiction; Young adult fiction; Radio and television novels